One-Dimensional Tunable Josephson Metamaterials - Butz, Susanne (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2014)
This thesis presents a novel approach to the experimental realization of tunable, superconducting metamaterials. Therefore, conventional resonant meta-atoms are replaced by meta-atoms that contain Josephson junctions, which renders their resonance frequency tunable by an external magnetic field. This tunability is theoretically and experimentally investigated in one-dimensional magnetic and electric metamaterials. For the magnetic metamaterial, the effective, magnetic permeability is determined.